IMPACT OF FEEDING FREQUENCY AND DIET RATIONING ON BIVOLTINE SILKWORM REARING IN GANGETIC PLAINS OF WEST BENGAL - DAS, S.; SAHA, A.K.; SAHU, P.K.; SHAMSUDDIN, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1998)
Biovoltine silkworm rearing has been conducted in different seasons with different feeding frequencies (2, 3, 4 & 5 times daily) and with different quantities of food rationing (10%, 20% and 30% rationing from optimum quantity) in 5th instar of larval life. Rearing, reeling and reproductive performances have been studied. The investigation reveals that thrice feeding daily and 10% rationing of food can easily be practiced in commercial biovoltine rearing in the Gangetic plains of West Bengal, which will help in upgrading rearing economy in form of saving manpower as well as preventing wastage of leaf during rearing.